Effect of Rhizobacteria and Palm Mill Byproducts on the Growth of Oil Palm Seedlings in a Pre-Nursery - Hastuti, Pauliz Budi; Wilisiani, Fariha; Gunawan, Sri; Lumban Gaol, Jhon Lewis; Setyawan, Heri (KnE Life Sciences, 2022)
Plant growth-promoting rhizobacteria (PGPR) is a type of microbe that can boost root development and plant growth by interacting with plant roots. The goal of this study was to examine how oil palm mill byproducts and PGPR can affect oil palm seedling growth in a pre-nursery. The study was conducted using a completely randomized design with factorial treatments. The empty oil palm bunches (EFB) were divided into three levels: soil:compost EFB (1:1), soil:ash EFB (1:1), and a control soil. The second variable was the PGPR dose, which was divided into three levels: chemical fertilizer (control), 20 ml, and 30 ml. Each treatment combination was repeated five times. The research findings were analyzed using analysis of variance to determine the true difference between the treatments tested using Duncan’s multiple range test at 5%. There was no interaction between the administration of EFB and the dose of PGPR in the growth of pre-nursery oil palm seedlings, according to the findings. Oil palm seedlings grew well in EFB compost in a pre-nursery setting. In pre-nursery palm head seedlings, PGPR application at a dose of 20 ml was able to provide good growth. Keywords: Pre-nursery, Empty Fruit Bunch, Organic Fertilizer, PGPR